Early adverse childhood experiences and later delinquency: considering the role of middle childhood risk factors - Reese, Braden (Deviant behavior, 2024)
Evidence suggests that adverse childhood experiences (ACEs) are associated with adolescent and adult delinquency. Simultaneously, studies have identified an association between middle childhood risk factors and subsequent delinquency. However, the research on how the relationship between early ACEs and adolescent delinquency is affected by middle childhood risk factors for delinquency is sparse. The current study addresses this, and other important gaps in existing ACE literature by using data from the Future of Families and Child Wellbeing Study (FFCWS; n = 3,444), a national urban birth cohort, to analyze how different levels of exposure to early ACEs (by age five) are associated with delinquency and to explore how multiple middle childhood risk factors (low self-control, prior delinquency, material hardship, experiences with bullying, and more recent ACE exposure) might mediate these processes. Findings suggest that two or more ACEs is significantly associated with increased rates of adolescent delinquency and that the association grows stronger as ACEs accumulate. Further, later ACEs, low self-control and prior delinquency mediate some of this relationship.